2020
DOI: 10.14569/ijacsa.2020.0111134
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of an Instrument to Assess Undergraduates’ Computational thinking Proficiency

Abstract: The potentiality of computational thinking (CT) in problem solving has gained much attention in academic communities. This study aimed at developing and validating an instrument, called Hi-ACT, to assess CT ability of university undergraduates. The Hi-ACT evaluates both technical and soft skills applicable to CT based problem solving. This paper reports a pilot study conducted to test and refine the initial Hi-ACT. Survey method was employed through which questionnaire comprising of 155 items was piloted among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…Nevertheless, there is always an urge to distinguish ways to envision the measurement of CT across all disciplines. Consequently, the issue of assessment in current studies was found lacking compared to the studies investigating approaches to teach CT (Sondakh et al, 2020b). On the other hand, an instrument from the west may not suitable for use in Malaysia due to cross cultural differences.…”
Section: Literature Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, there is always an urge to distinguish ways to envision the measurement of CT across all disciplines. Consequently, the issue of assessment in current studies was found lacking compared to the studies investigating approaches to teach CT (Sondakh et al, 2020b). On the other hand, an instrument from the west may not suitable for use in Malaysia due to cross cultural differences.…”
Section: Literature Reviewmentioning
confidence: 85%
“…However, adaptation of CT concepts in everyday life are not going to be easy and require thorough study (Sondakh et al, 2020a). Most of the attention on embedding CT during the past decade has centered on integration of CT skill in students with only little prominence about their perception, feeling or attitude towards the application of CT in problem solving across 2 / 15 various discipline or specifically in daily life (Sondakh et al, 2020b). Thus, development of an instrument to measure students' disposition towards CT is required.…”
Section: Introductionmentioning
confidence: 99%
“…In the cognitive domain, the authors consider some of the core skills, such as problem-solving, abstraction and decomposition, but also include a mix of general thinking skills such as reasoning, reflection, metacognition, and evaluation (Tang et al, 2020a). Attitudes and affective dispositions are used in other framings of CT as complements to the cognitive domain of CT (Sondakh et al, 2020; Tang et al, 2020a, 2020b). Although attitudes can impact students’ engagement with learning, it is difficult to distinguish specific learning opportunities offered in the context of CT (Velázquez-Iturbide, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The Hi-ACT [34] was used as data collection instrument in this study. This scale comprises of 110 seven-point Likert type items and ten constructs.…”
Section: Instrumentmentioning
confidence: 99%